The communication strategy of the government procurement of goods and services agency (LKPP) in socializing the use of e-catalogue to promote the transparency - Herman Purba; Rizaldi Parani; Reni Sara Indrawati; Edo Rinaldo (LP2M Universitas Sarjanawiyata Tamansiswa, 2023)
The Government Procurement of Goods and Services Agency (LKPP) has presented the E-Catalogue service, which is aimed at creating transparent governance of government procurement of goods and services, involving community participation in monitoring, as well as being a provider that markets goods and services. To achieve these goals, LKPP needs to implement an appropriate communication strategy in disseminating the use of the E-Catalogue. The approach in this study is qualitative and is supported by the use of the case study method. The data in this study were collected through in-depth interviews, observation, and literature review. The data were then processed through coding techniques to draw conclusions. The study found several communication strategies that have been implemented by LKPP, including setting rules and distributing circulars, creating content on websites and social media, publishing articles in mass media, using social media, forming working groups, providing assistance to regional governments, providing consulting services, and also providing routine training for government institutions and service providers. The authors also found that the communication strategy implemented by LKPP has been well implemented. This can be seen from the increase in the number of products listed in the E-Catalogue and the goods and service providers involved. However, several obstacles such as infrastructure, human resources, understanding and ease of use of the E-Catalogue continue to remain, which must be addressed by LKPP.